Kontribusi Pemikiran Islam KH. A. Wahab Chasbullah tentang Konsep Berbangsa dan Bernegara di Indonesia - Abdul Rochim Machfudz; Dzulkifli Hadi Imawan (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
KH. A. Wahab Chasbullah is one of the Indonesian Islamic figures who lived in several historical eras of the journey of the Indonesian state, starting from the colonialism era, the independence era, the Old Order political era to the New Order political era. In every history of the political journey of the establishment of the Indonesian state, there are many ego interests between groups of Indonesians that can lead to conflict and tension among the children of the nation. This paper discusses the thoughts and ideas of KH. A. Wahab Chasbullah based on Islamic religious norms in the life of the Indonesian nation and state. Using the descriptive-analytic method and the maqashid ash-shari'ah approach, this article describes KH. A. Wahab Chasbullah's thinking model that is characterised by ahlus sunnah wal jama'ah with the tradition of pesantren religious studies. The contribution of KH. A. Wahab Chasbullah's Islamic thought is reflected in his thoughts on love for the homeland, the relationship between religion and the state and respect for local traditions and culture.